Pengaruh Kualitas Layanan Customer Service Terhadap Kepuasan Nasabah di Bank Rakyat Indonesia Unit Simpang IV Sipin Kota Jambi - Ridho Guntoro; Endah Tri Kurniasih; Faradilla Herlin (Universitas Batanghari, 2020)
The quality of service is a unique phenomenon, because the dimensions and indicators can differ among the people involved in the service. BRI Unit Simpang IV Sipin focuses on the quality of service provided in the form of speed and convenience given to customers. One form of problem that becomes a phenomenon experienced by customers and needs to be the main concern for banks to always be improved and improved so that the bank's performance becomes more productive is the queue, queueing or waiting line that occurs while waiting for banking services. This research aims to know and analyze the characteristics of BRI Unit Simpang IV Sipin Jambi city and to know and analyze the effect of customer satisfaction on customer service BRI Unit Simpang IV Sipin Jambi City. In this study the data used is primary data. This primary data was obtained from live interviews using questionnaires on research objects with the time the study was conducted in January - March 2020. The result of this research is that the Quality of Customer Service service has an effect on the customer satisfaction of BRI Unit Simpang IV Sipin Jambi City. The amount of influence of the training is 19.8%. The service provided by BRI Customer Service Unit Simpang IV Sipin must still be maintained or worthy to be improved again, this can affect the satisfaction of existing customers.